Effect of carbon fiber inclusions on polymeric transfer film formation on steel. (5th January 2022) - Puhan, Debashis; Jiang, Shaoli; Wong, Janet S.S.
Abstract: High performance polymers (HPPs) with good tribological properties are commonly used in dry contacts, where their tribological performance often depends on properties of polymeric transfer materials (transfer layers) on counterfaces. Most HPPs suffer from high temperature degradation due to frictional heating, leading to excessive deformation and wear. Incorporating thermally conducting fillers increases their thermal conductivity and mechanical strength. The impact of these fillers on formation and properties of transfer layers, however, is unclear. In this work the effect of short carbon fiber fillers (CFs) on the nature of the transfer layers and tribological performance of polyetheretherketone (PEEK) and polyetheretherketone-polybenzimidizole (PBP) against steel were investigated at temperature up to 300 °C. Transfer layers of CF reinforced PEEK and PBP contain CF-related materials, resulting in a reduction of friction as compared to neat PEEK and PBP, especially around the glass transition temperature of PEEK ( T g − P E E K ) when the transfer layer is relatively thick. While the inclusion of CFs increases the bulk thermal conductivity of polymer composites, the average contact temperature is not affected. Rather, local hot spots are generated. As a result, their transfer layers may have formed more readily and have undergone more severe degradation than those from neat polymer. At 300 °C, the PBP + CF transfer layer is thin possibly due to abrasion by CFs dislodged from the matrix. The improvement in the wear resistance due to CF inclusion is observed with PBP up to 300 °C due to its improved mechanical strength. PEEK + CF however suffers higher wear than PEEK below T g − P E E K . Above T g − P E E K, a thick transfer layer is formed and the wear of PEEK + CF reduces. Graphical abstract: Image 1